Design Strategies for Responsive Fluorine‐19 Magnetic Resonance Probes Using Paramagnetic Metal Complexes. Issue 2 (2nd September 2022) - Ryan, Raphael T.; Scott, Kathleen M.; Que, Emily L.
Abstract: Magnetic resonance imaging (MRI) is a powerful and widely used in vivo imaging technique that enables whole body imaging without ionizing radiation. In clinical practice, 1 H MRI is employed for imaging anatomical and physiological states via monitoring of protons in water and lipids. In order to monitor biochemical processes at the molecular level, several research groups are exploring responsive MRI agents that alter their signal upon interaction with an analyte or biological environment of interest. Fluorine ( 19 F) MRI agents are promising due to the 19 F nucleus having similar magnetic resonance (MR) properties to proton and the absence of endogenous 19 F in living systems, resulting in no background signal. In order to make responsive 19 F MR agents for molecular imaging and analysis, fluorinated platforms must be developed in which their 19 F MR signal changes after interacting with a target analyte. A promising strategy is to use paramagnetic metals to modulate the 19 F MR signal by altering the relaxation rates and/or chemical shift of an appended 19 F imaging tag. In this concept, we provide an overview of the theoretical principles and molecular design strategies that have been exploited in the design of responsive 19 F MR agents, with a specific focus on agents based on small molecule paramagnetic metal ion chelates. Abstract : Responsive fluorine ( 19 F) MRI agents can be created by using paramagnetic metals that quench or perturb the 19 F signal of the coordinated fluorinated ligand. Through careful ligand design, these agents can interact with analytes and abnormal cellular conditions to change their magnetic properties to produce a "turn on" mechanism or alter their 19 F signal.